Therapeutic Potential of Moringa pterigosperma Extract in Alloxan-Induced Type 2 Diabetic Rats: Endocrine and Metabolic Modulation with a Focus on LH, Testosterone, and Glucose-Insulin Homeostasis - Asia Ali Hamza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Diabetes mellitus type 2 is a chronic metabolic disorder characterized by persistent hyperglycemia and endocrine dysfunction, including disturbances in luteinizing hormone, testosterone, and insulin levels. Moringa pterygosperma, known for its antidiabetic, antioxidant, and anti-inflammatory properties, has been explored for its therapeutic potential in mitigating diabetes-induced complications.Objective: The present study aimed to estimate the effects of Moringa pterygosperma extraction on endocrine and metabolic parameters against the diabetic rats induced by alloxan, by the mensurate the on LH, testosterone, glucose, and insulin levels.Methods: Forty adult male albino Wistar rats were used in the present study which was divided into four equal groups: Control, Negative Control, Treatment one which used 100 mg/kg extract, and Treatment two which used 200 mg/kg extract). Diabetes was induced with alloxan monohydrate (100 mg/kg). After 41 days, serum samples were analyzed for testosterone, LH, glucose, and insulin concentrations. Results: The NC group showed significant reductions in testosterone (0.0926 ± 0.0081 ng/mL) and insulin (0.560 ± 0.09274 µIU/mL) levels, with increased luteinizing hormone (0.592 ± 0.03 ng/mL) and glucose (464.6 ± 18.71 mg/dL) concentrations, indicating severe endocrine and metabolic disruptions. Treatment with Moringa pterygosperma extract significantly improved these parameters in a dose-dependent manner. The T2 group exhibited near-normal levels of testosterone (0.1769 ± 0.01 ng/mL), insulin (2.140 ± 0.1435 µIU/mL), LH (0.3163 ± 0.063 ng/mL), and glucose (105.8 ± 9.34 mg/dL).